Analysis of Operational Efficiency at Unsignalized Intersections in Pontianak City - Irwandi Irwandi; Anastasia Caroline Sutandi; Elsa Tri Mukti (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Congestion in Pontianak City significantly impacts traffic flow, affecting both efficiency and comfort of road transit. The city's unsignalized intersections, crucial for managing vehicle flow from multiple directions, are under scrutiny for their performance. A study using the Indonesian Road Capacity Guidelines (IRCG) has assessed intersections, that the degree of saturation often exceeds acceptable limits, leading to congestion and increased delays. The research highlights that the current capacity of these intersections is insufficient to handle the growing traffic demand. For instance, under maximum traffic flow conditions, one intersection recorded a total traffic flow of 2,978.20 pcu/hour against a capacity of 2,716.40 pcu/hour, resulting in a degree of saturation of 1.096. This indicates a need for interventions like installing traffic signals or modifying road geometry to enhance flow efficiency. Despite these findings, the analysis of existing conditions specific unsignalized intersections showed a level of service value of E and F, suggesting that these intersections currently require immediate improvements. However, to further improve intersection performance, recommendations include reducing side obstacles, enhancing road geometry, and installing two-phase traffic signals, which offer the highest capacity with minimal delay. These measures aim to ensure that Pontianak City's transportation infrastructure can effectively.